2023
DOI: 10.1177/13506501231161379
|View full text |Cite
|
Sign up to set email alerts
|

Micropolar lubricant effects on the performance of partial journal bearings

Abstract: Present work deals with the computation of static performance of partial journal bearing, operated with micropolar lubricant. The non-dimensional Reynolds equation governs the lubricant flow in clearance space and finite element method is used to solve it. Static characteristics including bearing load capacity, attitude angle, friction force, friction factor, and side flow are presented. Input parameters are chosen such as partial angles 120° and 180° and a width-diameter ratio (1.0), for a range of micropolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In the open literature, the authors could not find any work dealing with the computation of the stability performance of a partial journal bearing with micropolar lubricant. The authors found only the work of Sharma et al (2023); they presented the static performance of micropolar lubricated partial arc bearings.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the open literature, the authors could not find any work dealing with the computation of the stability performance of a partial journal bearing with micropolar lubricant. The authors found only the work of Sharma et al (2023); they presented the static performance of micropolar lubricated partial arc bearings.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of recent work by Sharma et al (2023), the authors have chosen the dynamic stability analysis of such bearings, so that the results obtained may be helpful to designers and researchers for elastohydrodynamic analysis and thermal analysis of partial journal bearings with micropolar lubrication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation